Erasmus Darwin and the Romantic Poets - King-Hele, D. author. aut Link
VII, 294 p.
Keywords: Erasmus Darwin (1731-1802) had the highest reputation among living English poets during much of the 1790s, through the great success of his long poem in rhyming couplets, The Botanic Garden, published complete in 1792. In this new book Desmond King-Hele shows in convincing detail how Darwin greatly influenced five major English Romantic poets, Blake, Wordsworth, Coleridge, Shelley and Keats, and many other poets of the time, such as Crabbe and Campbell (but not Byron).